MEMBUAT PENONTON BIOSKOP CGV KOTA PROBOLINGGO PUAS DENGAN PROMOSI, HARGA, DAN KUALITAS PELAYANAN - Junaidi; Syarif Hidayatullah Elmas, Muhammad; Tumini; Rizal, Saiful (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2025)
This study aims to analyze the satisfaction of CGV Kota Probolinggo audiences by involving the variables of promotion, price, and service quality. The research method used is quantitative research with a causal approach aimed at testing the cause-and-effect relationship between the variables studied. The research process involved descriptive analysis and inferential testing (data quality testing, research model testing, and hypothesis testing), using 108 respondents with AMOS software. The results of the study indicate that effective promotion, competitive pricing, and excellent service quality significantly increase the satisfaction of CGV cinema audiences in Probolinggo City. Targeted promotions increase public awareness of CGV and the films being shown, appropriate prices add value to the viewing experience, and quality service—from staff friendliness to comfortable facilities—meets audience expectations. Thus, with effective promotion, the awareness of the people of Probolinggo City regarding the presence of CGV and the films currently being screened can be increased.